Effect of Salinity on Larval Rearing of Pacu, Piaractus mesopotamicus, a Freshwater Species - Jomori, Rosangela K. [UNESP]; Luz, Ronald K. [UNESP]; Portella, Maria Celia [UNESP] (Wiley-Blackwell, 2012)
The aim of this study was to evaluate the growth and survival of pacu, Piaractus mesopotamicus, larvae reared in different salinities and to determine the Artemia nauplii life span in freshwater and in saline water. First feeding 5-d-old pacu larvae were reared in freshwater or at 2, 4, 6, 8, 10, 12, and 14 ppt salinities. The larvae were reared in 1.5-L aquaria at a density of 10 larvae/L with three replicates per treatment. After 10 d of rearing, significant differences (P < 0.05) were observed for growth and survival. Larval growth was higher at 2 and 4 ppt, and survival at 2 ppt was 100%. In freshwater and at 4, 6 and 8 ppt, the survival was 91.1, 93.3, 73.3, and 39.9%, respectively. At higher salinities, there was 100% mortality after 2 h (12 and 14 ppt) and 8 h (10 ppt) of exposure. The slightly saline water of at least 2 ppt increased the Artemia nauplii life span compared to the life span in freshwater. Later, in a second trial, 5-d-old pacu larvae were reared in freshwater and at 2 and 4 ppt salinities during the first 5 or 10 d of active feeding, and then the fish were transferred to freshwater. At the end of 15 d, larval growth was lower in freshwater (42 mg) than in treatments 2 and 4 ppt (5963 mg). The abrupt transfer of fish from freshwater to slightly saline water and the return to freshwater did not affect the survival rates (8997%). The larvae were able to adapt to these saline environments and handle abrupt changes in salt concentration. We concluded that salinity concentration of 2 ppt can be used for pacu larval rearing, allowing the Artemia nauplii lifetime to last longer and cause faster fish growth.